Redefining the biological basis of lineage-ambiguous leukemia through genomics: BCL11B deregulation in acute leukemias of ambiguous lineage - Montefiori, Lindsey E.; Mullighan, Charles G. (Best practice & research. Clinical haematology, 2021)
Acute leukemias of ambiguous lineage (ALAL), including mixed phenotype acute leukemia (MPAL) and related entities such as early T-cell precursor acute leukemia (ETP-ALL), remain diagnostic and clinical challenges due to limited understanding of pathogenesis, reliance of immunophenotyping to classify disease, and the lack of a rational approach to guide selection of appropriate therapy. Recent studies utilizing genomic sequencing and complementary approaches have provided key insights that are changing the way in which such leukemias are classified, and potentially, treated. Several recurrent genomic alterations define leukemias that straddle immunophenotypic entities, such as ZNF384-rearranged childhood B-ALL and B/myeloid MPAL, and BCL11B-rearranged T/myeloid MPAL, ETP-ALL and AML. In contrast, some cases of MPAL represent canonical ALL/AML entities exhibiting lineage aberrancy. For many cases of ALAL, experimental approaches indicate lineage aberrancy arises from acquisition of a founding genetic alteration into a hematopoietic stem or progenitor cell. Determination of optimal therapeutic approach requires genomic characterization of uniformly treated ALAL patients in prospective studies, but several approaches, including kinase inhibitors and BH3 mimetics may be efficacious in subsets of ALAL.